Contemporary Reflections on Business Ethics - Duska, Ronald F. (Issues in Business Ethics, 2007)
Ronald F. Duska, who began his career as a philosopher, has, over the last 30 years, established himself as one of the leading scholars in the field of business ethics. In the past decade, he has concentrated on ethics in the financial services industry because of his affiliation with The American College in Bryn Mawr, Pennsylvania, an institution that specializes in educating financial services professionals. This affiliation gives Duska regular interaction with producers, managers, and top executives in the financial services industry. This book includes a selection of the articles Duska has written throughout the years on ethics, business ethics, teaching ethics, agency theory, postmodernism, employee rights, and ethics in accounting and the financial services industry. The articles reflect Duska's underlying philosophical concerns and their application to the real-world challenges of practitioners-an overarching method that might be called an Aristotelian common-sense approach to ethical decision making.